Pressure leaching of wolframite using a sulfuric-phosphoric acid mixture. (1st August 2021) - Luo, Yiwei; Chen, Xingyu; Zhao, Zhongwei; Liu, Xuheng; Li, Jiangtao; He, Lihua; Sun, Fenglong
Highlights: Decomposing wolframite in a pressurized leaching system. Compared with atmospheric leaching, this method can get a higher leaching efficiency. Temperature has a significant effect on leaching. The final leaching efficiency of wolframite is more than 98%. Abstract: In this paper, tungsten was extracted from wolframite using sulfuric-phosphoric acid mixtures. During leaching, wolframite was decomposed under acidic conditions, and phosphotungsten heteropoly acid was formed by the complexation of tungsten and phosphorus. The XRD results showed that after wolframite leaching, the residue contained unleached wolframite, quartz, small amounts of calcium sulfate (anhydrite) and phosphotungstate salts. When the concentration of H2 SO4 was 2.5 mol/L, the concentration of H3 PO4 was 2.0 mol/L, the liquid–solid ratio was 10 mL/g, the reaction time was 4 h, and the reaction temperature was 140 ℃, the maximum leaching efficiency of tungsten reached 98.8%. This method broadens the applicability of the sulfuric-phosphoric mixed acid system to the decomposition of wolframite under pressure hydrometallurgical conditions.